Mathematical communication ability in the application of matrices in informatics engineering - Lestari, Santi Arum Puspita (AIP conference proceedings, 2021)
Matrix is one of the subjects studied in the scope of informatics. It is because of the matrix as support in coding. The use of matrices in information technology cannot be done directly, but matrices must be modeled first into the programming language. This research is a mixed-methods between quantitative and qualitative research conducted on students of Informatics Engineering Study Program. The sample used was 120 students in the second semester who were selected by purposive sampling. The purpose of this research is to find out the extent of students’ communication ability in the application of matrices in the field of informatics. The data were collected in the form of paper assignments regarding the application of the matrix within the scope of informatics engineering. Data analysis to measure mathematical communication ability is done in two ways. The first one is the assessment of the content or content of papers that fit the criteria, and the next one is student presentations explaining the results of the paper. In addition, interviews also conducted with students regarding the application of the matrix. After being analyzed, the result says that the mathematical communication ability of students is quite good. Mathematical communication ability which included in this study is a representation, reading, and writing. Most of the students have understood and can communicate matrix material with its application in Informatics Engineering. However, students have not been able to apply it independently because they have not studied programming material further. Thus, the mathematics communication ability needed in Informatics Engineering is to read matrix symbols, represent matrix symbols in informatics symbols, and then write them back into the programming language.